Immigration and Status Exchange in Australia and the United States - Kate H. Choi; Marta Tienda; Deborah Cobb-Clark; Mathias Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
The claim that marriage is a venue for status exchange of achieved traits, like education, and ascribed attributes, notably race and ethnic membership, has regained traction in the social stratifi cation literature. Most studies that consider status exchanges ignore birthplace as a social boundary for status exchanges via couple formation. This paper evaluates the status exchange hypothesis for Australia and the United States, two Anglophone nations with long immigration traditions whose admission regimes place diff erent emphases on skills. A log-linear analysis reveals evidence of status exchange in the United States among immigrants with lower levels of education and mixed nativity couples with foreign-born husbands. Partly because Australian educational boundaries are less sharply demarcated at the postsecondary level, we fi nd weaker evidence for the status exchange hypothesis. Australian status exchanges across nativity boundaries usually involve marriages between immigrant spouses with a postsecondary credential below a college degree and native-born high school graduates.
Keywords: F22; I24; 330; Status exchange; immigration; educational assortative mating